2017
DOI: 10.1259/bjr.20160686
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for radiation-induced hypothyroidism prediction in nasopharyngeal carcinoma after treatment

Abstract: The authors Ren Luo and Mei Li contributed equally to this work.Objective: The aim of this study was to develop a nomogram for radiation-induced hypothyroidism (RHT) prediction. Methods: We collected data from 164 patients with nasopharyngeal carcinoma (NPC) in our previous prospective study. Biochemical hypothyroidism was defined as a serum thyroid-stimulating hormone level greater than the normal value. We collected both clinical and dose-volume factors. A univariate Cox regression analysis was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…In accordance with the previous studies [ 3 , 8 , 9 , 16 , 19 , 22 ], the female gender and V 50 were identified as risk factors in this study. It remains controversial [ 9 , 29 31 ] whether chemotherapy is a predictor of RHT.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with the previous studies [ 3 , 8 , 9 , 16 , 19 , 22 ], the female gender and V 50 were identified as risk factors in this study. It remains controversial [ 9 , 29 31 ] whether chemotherapy is a predictor of RHT.…”
Section: Discussionsupporting
confidence: 90%
“…It remains controversial [ 9 , 29 31 ] whether chemotherapy is a predictor of RHT. However, in our previous study [ 22 ], chemotherapy plays a major role in the nomogram for biochemical HT prediction in NPC patients. In this study, only one experienced biochemical HT among 19 patients who did not receive chemotherapy, and chemotherapy was identified as an independent predictor in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other parameters predicting a higher rate of hypothyroidism included younger age [ 5 , 11 , 12 ], female sex [ 13 , 14 ], mean radiation dose to the thyroid [ 6 ] and small thyroid volume [ 5 , 6 , 10 , 12 , 15 ]. The use of chemotherapy, and autoimmune disease, may also be associated with hypothyroidism [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, scholars here and abroad hold different opinions on the relationship between thyroid dose-volume and HT. One study suggested that the thyroid minimum dose, mean dose, and V 25 -V 60 are significantly associated with HT [21]. Sommat et al [22] have suggested that the thyroid V 40 is closely related to HT, where the incidence of radiation-induced HT in the thyroid V 40 ≤ 85% and thyroid V 40 > 85% groups was 21.4% (3/14) and 61.4% (54/88), respectively.…”
Section: Hypothyroidism and Thyroid Dosementioning
confidence: 99%